Pengenalan Pendidikan Seksual Melalui Media Audio-Visual pada Anak Usia 5-6 Tahun - Widyastuti, Listya; Khasanah, Ismatul; Rakhmawati, Ellya; Prasetyo, Agung (Universitas PGRI Semarang, 2023)
AbstractThe background of the research is that the high rate of sexual violence every year in Indonesia makes the community uneasy about the conditions of child development. This makes researchers interested in researching the prevention of child sexual violence through sexual education using audio-visual learning media. The focus of the research is the introduction of sexual education through audio-visual media for children aged 5-6 years at Kuncup Sari Kindergarten Semarang. The research objective was to provide an understanding of the importance of introducing sexual education to children, and information on the introduction of sexual education to children aged 5-6 years through audio-visual media. Researchers used a descriptive qualitative research approach. The research data consisted of four children consisting of two boys and two girls. Data collection techniques through observation, interviews, documentation and triangulation of sources. The results showed that the introduction of sexual education to children aged 5-6 years at Kuncup Sari Kindergarten Semarang can be given through audio-visual media. The introduction of sexual education that can be given is in the form of gender differences, habituation of toilet training, introducing parts of the body that can and cannot be touched, introducing parts of the body that must be covered with clothes, identifying negative behaviors of others, and how to refuse invitations from strangers.Keywords: Sexual Education, Audio- Visual Media, Children Aged 5-6 Years.AbstrakLatar belakang penelitian ini adalah tingginya angka kekerasan seksual pada anak di Indonesia khususnya di Semarang. Salah satu upaya yang dapat dilakukan untuk mencegah kekerasan seksual anak melalui pendidikan seksual. pendidikan seksual yang diajarkan pada anak usia 5-6 tahun dapat dilakukan melalui bantuan media pembelajaran, yaitu media auido-visual. permasalsah dalam penelitian ini adalah kasus kekerasan seksual anak semakin meningkat setiap tahunnya, salah satu upaya pencegahan kekerasan seksual melalui pendidikan seksual, pendidikan seksual yang diajarkan pada anak usia 5-6 tahun melalui media pembelajran, yaitu media audio-visual. Pendekatan dalam penelitian ini menggunakan deskriptis bersifat kualitatif. Data dalam penelitian ini diperoleh melalui observasi, wawancara, dan dokumentasi. Teknik analisis yang digunakan berupa reduksi data, penyajian data berupa teks deskriptif dan tabel, penarikan kesimpulan dan verification. Hasil penelitian menunjukkan pengenalan pendidikan seksual pada anak usia 5-6 tahun di TK Kuncup Sari Semarang dapat diberikan melalui media audio-visual. Materi yang dapat diberikan pada pengenalan pendidikan seksual bagian tubuh yang boleh dan tidak boleh disentuh. bagian tubuh yang harus tertutup pakaian, mengidentifikasikan perilaku negatif orang lain, cara menolak ajakan orang tidak dikenal.Kata kunci: Pendidikan Seksual, Media Audio-Visual, Anak Usia 5-6 Tahun.